Study Relation of the Fibrinogen and Homocysteine with Coronary Heart Disease - Nasir Kareem Dhahir (Journal of Global Pharma Technology, 2016)
Because of wide spread chronic infections, especially in patients who have  the coronary heart diseases (CHD), and by measuring the inflammatory factors as a biomarker related to this disease including, fibrinogen, homocystein, and the relation of the disease with some risk factors such as the age, blood pressure, body mass index and blood sugar. The study was carried out in the Baqubah teaching hospital in a period from (September/ 2017) to (September/ 2018) in patients who are admitted to coronary care unit (CCU), including ( 35 patients with myocardial infarction, 24 males , 11 females), and( 35 patients with angina pectoris, 19 males, 16 females). The both groups are compared with other healthy group consisting of 20 persons (12 males, 8 females). The range of age was (40-70 years).  The principles of method used is by (7 ml) of blood from each patient to estimate the level of serum fibrinogen by using coagulation homeostasis analysis device, and the homocystein is measured by using ELISA technique, and the measuring of the other biochemistry factors by using Cobas Integra 400 plus device. The results of the study showed that, there is a significant value difference  p < 0.05 of fibrinogen, homocystein, body mass index, systolic blood pressure, fasting blood sugar of patients with myocardial infarction and angina pectoris compared to control (healthy), the levels of the fibrinogen and homocystein will elevated with extreme of the age and increase body mass index (BMI), also there is a positive correlation (r=0.04) and in significant value (p=0.70) for homocystein and systolic blood pressure, and the correlation (r=0.08) in significant value (p=0.46) for homocystein and diastolic blood pressure, while the levels of the fibrinogen to systolic blood pressure is(r= - 0.19) in significant value (p=0.07)but the diastolic blood pressure (r= - 0.09) in significant value (p=0.35). Also there is less positive correlation of fibrinogen to blood sugar (r=0.039) in significant value (p=0.71) while there is a negative correlation (r= - 0.04) in significant value (p=0.72) between homocystein and blood sugar. Aim of the study: to investigate the effect of levels of the inflammatory factors involving the fibrinogen and homocystein with relation to coronary heart diseases and study the correlation with other risk factors such as age, blood pressure, body mass index and blood sugar.Keywords: Fibrinogen, Homocystein, Coronary heart diseases (CHD), Body mass index (BMI), Myocardial infarction, Angina pectoris, Blood sugar,  Cardio vascular diseases(CVD).